Global energy fundamentals : economics, politics, and technology - Tagliapietra, Simone (Cambridge : Cambridge University Press, 2020)
This book provides a rigorous, concise guide to the current status and future prospects of the global energy system. As we move away from fossil fuels and toward clean energy solutions, the complexity of the global energy system has increased. Tagliapietra cuts through this complexity with a multidisciplinary perspective of the system, which encompasses economics, geopolitics, and basic technology. He goes on to explore the main components of the global energy system - oil, natural gas, coal, nuclear energy, bioenergy, hydropower, geothermal energy, wind energy, solar energy, marine energy - as well as energy consumption and energy efficiency. It then provides an in-depth analysis of the pivotal issues of climate change and of energy access in Africa.
Title from publisher's bibliographic system (viewed on 17 Jul 2020).
Keywords: Power resources -- Environmental aspects; Energy industries -- Environmental aspects; Renewable energy sources; Climatic changes